Reliability Assessment of Various Sonographic Techniques for Evaluating Carpal Tunnel Syndrome. (9th October 2015) - Junck, Anthony D.; Escobedo, Eva M.; Lipa, Bethany M.; Cronan, Michael; Anthonisen, Colleen; Poltavskiy, Eduard; Bang, Heejung; Han, Jay J.
Abstract : Objectives: The aim of this study was to determine the intra‐ and inter‐rater reliability of sonographic measurements of the median nerve cross‐sectional area in individuals with carpal tunnel syndrome and healthy control participants. Methods: The median nerve cross‐sectional area was evaluated by sonography in 18 participants with carpal tunnel syndrome (18 upper extremities) and 9 control participants (18 upper extremities) at 2 visits 1 week apart. Two examiners, both blinded to the presence or absence of carpal tunnel syndrome, captured independent sonograms of the median nerve at the levels of the carpal tunnel inlet, pronator quadratus, and mid‐forearm. The cross‐sectional area was later measured by each examiner independently. Each also traced images that were captured by the other examiner. Results: Both the intra‐ and inter‐rater reliability rates were highest for images taken at the carpal tunnel inlet (radiologist, r = 0.86; sonographer, r = 0.87; inter‐rater, r = 0.95; all P < .0001), whereas they was lowest for the pronator quadratus ( r = 0.49, 0.29, and 0.72, respectively; all P < .0001). At the mid‐forearm, the intra‐rater reliability was lower for both the radiologist and sonographer, whereas the inter‐rater reliability was relatively high ( r = 0.54, 0.55, and 0.81; all P < .0001). Tracing of captured images by different examiners showed high concordance for the median cross‐sectional area at the carpal tunnel inlet ( r = 0.96–0.98; P < .0001). Conclusions: The highest intra‐ and inter‐rater reliability was found at the carpal tunnel inlet. The results also demonstrate that tracing of the median nerve cross‐sectional area from captured images by different examiners does not contribute significantly to measurement variability.